Age and weight no bars for congenital diaphragmatic hernia - Debashree Priyadarshini; Ipsita Sahoo; Mrutunjay Dash (Indian Pediatrics Case Reports, 2023)
Background: Congenital diaphragmatic hernia (CDH) of the left side may clinically manifest as chronic wheezing or gastrointestinal reflux disease in older children. Misdiagnosis of CDH is common in later age groups. Case Description: An 11-year-old boy presented to the outpatient department with a history of intermittent cough for 2 years and acid reflux. He was treated with a case of bronchial asthma and received symptomatic treatment for the same, but he continued to have symptoms without much relief. On examination, he was found obese with no signs of respiratory distress. On auscultation, there were reduced breath sounds in the left inframammary, infra-axillary, and infrascapular region with a normal examination of other systems. Management: The chest X-ray was suggestive of heterogeneous opacities engulfing more than half of the left hemithorax in the middle and lower zone of the left lung area with nonvisualization of the left dome of the diaphragm and the presence of abdominal gas shadows in the opacity. Considering the possibilities of diaphragmatic hernia or eventration, high-resolution computed tomography of the thorax was done, and left-sided Bochdalek hernia was confirmed. The child underwent surgical repair uneventfully and was discharged home with no complications. Conclusion: An adolescent boy has a late diagnosis of left-sided CDH. Considering the wide spectrum of clinical presentation, a high index of suspicion is crucial for the diagnosis of CDH since it might develop into a life-threatening condition. An excellent prognosis can be achieved with early diagnosis and effective therapy.